Clinical Course of COVID-19 Infection in Patients Urgently Operated of Cardiac Surgical Procedures. Issue 4 (October 2020) - Garatti, Andrea; Castelvecchio, Serenella; Daprati, Andrea; Molfetta, Raffaella; Volpe, Marianna; De Vincentiis, Carlo; Parolari, Alessandro; Menicanti, Lorenzo
Abstract : Objective: The aim of this study was to describe the clinical course of a consecutive series of patients operated of urgent cardiac surgery during COVID-19 outbreak. Background: In Italy, COVID outbreak has mostly occurred in the metropolitan area of Milan, and in the surrounding region of Lombardy, and previously "conventional" hospitals were converted into COVID spokes to increase ICU beds availability, and to allow only urgent CS procedures. Methods: Among urgent CS patients (left main stenosis with unstable angina, acute endocarditis, valvular regurgitation with impending heart failure), 10 patients (mean age = 57 ± 9 years), despite a negative admission triage, developed COVID-pneumonia postoperatively, at a median of 7 days after CS. Results: Patients showed typical lymphopenia, higher prothrombotic profile, and higher markers of inflammation (ferritin and interleukin-6 values). At the zenith of pulmonary distress, patients presented with severe hypoxia (median PaO2 /FIO2 ratio = 116), requiring advanced noninvasive ventilation (Venturi mask and continuous positive airway pressure) in the majority of cases. All patients were treated with hydroxychloroquine, azithromycin, and low-molecular-weight heparin at anticoagulant dose. Overall in-hospital mortality was 10% (1/10), peaking 25% in patients who developed COVID pneumonia immediately after CS. The remaining patients, with late infection, were all discharged home without oxygen support, at a median of 25 days after symptom onset. Conclusions: As postoperative mortality in case of COVID pneumonia is not negligible, meticulous rules (precise triage, safe hospital path, high level of protection for health-care teams, prompt diagnosis of suspicious symptoms) should be strictly followed in patients undergoing CS during COVID pandemic. The role of therapies alternative to CS should be further assessed.